2016
DOI: 10.1016/s0140-6736(16)00204-x
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section surgical techniques: 3 year follow-up of the CORONIS fractional, factorial, unmasked, randomised controlled trial

Abstract: SummaryBackgroundThe CORONIS trial reported differences in short-term maternal morbidity when comparing five pairs of alternative surgical techniques for caesarean section. Here we report outcomes at 3 years follow-up.MethodsThe CORONIS trial was a pragmatic international 2 × 2 × 2 × 2× 2 non-regular fractional, factorial, unmasked, randomised controlled trial done at 19 sites in Argentina, Chile, Ghana, India, Kenya, Pakistan, and Sudan. Pregnant women were eligible if they were to undergo their first or seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…6 In this study, authors considered all women with a complete uterine rupture as cases (n = 175), and all women with two births with TOLAC at term and no uterine rupture as controls (n = 272). Confirming what was previously reported in the CORONIS trial, 4 there was no association between single-layer closure and uterine rupture at term.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…6 In this study, authors considered all women with a complete uterine rupture as cases (n = 175), and all women with two births with TOLAC at term and no uterine rupture as controls (n = 272). Confirming what was previously reported in the CORONIS trial, 4 there was no association between single-layer closure and uterine rupture at term.…”
supporting
confidence: 89%
“…A few years later, the publication of the CORONIS randomized controlled trial's results at 3 years followup contributed to a paradigm shift in clinical practice. 4 In this large study, the authors investigated the rates of pelvic pain, deep dyspareunia, hysterectomy, and outcomes of subsequent pregnancies in women undergoing cesarean section following blunt versus sharp abdominal entry, exteriorization of the uterus for repair versus intra-abdominal repair, single versus double layer closure of the uterus, closure versus nonclosure of the peritoneum, and chromic catgut versus polyglactin-910 for uterine repair. Interestingly and unexpectedly, there was no evidence of a difference in risk of abdominal hernias for blunt versus sharp abdominal entry, no evidence of a difference in risk of infertility or of ectopic pregnancy for exteriorization of the uterus versus intra-abdominal repair, no evidence of a difference in maternal death or a composite of pregnancy complications for single-versus doublelayer closure of the uterus, no evidence of a difference in any outcomes relating to symptoms associated with pelvic adhesions such as infertility for closure versus nonclosure of the peritoneum and, finally, no evidence of a difference in the main comparisons for adverse pregnancy outcomes in a subsequent pregnancy for chromic catgut versus polyglactin-910 sutures.…”
mentioning
confidence: 99%
“…The authors suggest that in the absence of clinical benefit, considerations such as cost and time savings should dictate appropriate technique. 15 We concur wholeheartedly with this logic. Omitting steps with no benefit are just as important as including those with benefit and critical to establishing a standardized technique.…”
Section: Why Standardize Cesarean Delivery Surgical Technique?mentioning
confidence: 60%
“…Since the previous systematic review by Dahlke et al in 2013, the CORONIS trial has reported short-term and long-term data for more than 15,000 women undergoing cesarean delivery randomized to three of five alternative surgical techniques. 4 , 13 15 There was no difference in outcomes related to cesarean delivery surgical technique including long-term outcomes such as subsequent uterine rupture (indicating that double layer uterine closure is not protective) or symptoms attributable to intra-abdominal adhesions (indicating that peritoneal closure is not protective). The authors suggest that in the absence of clinical benefit, considerations such as cost and time savings should dictate appropriate technique.…”
Section: Why Standardize Cesarean Delivery Surgical Technique?mentioning
confidence: 98%
“…[9] A collaborative study published in 2016, CORONIS, observed ~8 100 women during a 3-year follow-up and did not find any difference in the occurrence of pelvic pain, dyspareunia, bowel obstruction, bladder surgery, infertility and ectopic pregnancy, whether the peritoneum was closed with sutures or not. [11] Perhaps a longer follow-up of the CORONIS study in future might give clinicians the final answer to the fate of the peritoneum. A paradigm shift in practice cannot be succinctly advocated until the possible chronic sequelae have been assessed in studies incorporating longer follow-up periods.…”
Section: Discussionmentioning
confidence: 99%